Estudo da estrutura - atividade da norharmana, DHM-cumarina e riparinas I, II, III usando Espectroscopia eletrônica e cálculos teóricos. - Piedade, Claudenor de Souza (2009)
Norharman, Riparin I, II, III, and DHMC, molecules which can be found in natural products of the Amazon, have been studied with the spectroscopy of emission at 77K in the stationary state and resolved by the time, UV/visible spectroscopy, infrared spectroscopy, and calculations of the molecular orbital: Semi-empiric, HAM/3-CI, ZINDO/S-CI, PM3, AM1, RM1; Abinitio RHF/6-31G * and Density Functional Theory. Based on the results, it has been tried to make a relation between the chemical structure and the activity of each molecule, pondering the effects of the solvent and substitutes, and making the correlation between experimental and theoretical results. For NH and DHMC it was obtained, among others, its photophysical properties, and active species on the hydrophobic and hydrophilic vicinities, photoactive region, and nature of the excited electronic state of the lowest energy, solubility of species on micelles, and the species on action in the micelle interior. For the riparins, it was done a theoretical study with the TFD, by which it was concluded that the potency of the anti-hypertension effect and the muscle relaxation of these molecules have greatest contribution of the electronic structure than the molecular one. It was also observed that the TFD, in every case when it was used, produced results more close to experimental results than the semi-empiric calculation. The use of spectroscopic techniques in association with the theoretical calculations used in this work showed to be a very useful tool to the study of the relationship between the structure and the xiv activity of bioactive molecules. The spectroscopy of emission at 77K is clearly sensible for being a direct way for characterization of active species and sites of solubility in membranes models